Determinants of Audit Delay: The Influence of Internal and External Factors on the Company - Dessyana Suryawandari; Akhmad Afnan (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2025)
Several variables, including company size, audit opinion type, KAP size, audit duration, and financial ratios (such as profitability and solvency), may influence audit delay. The purpose of this study is to investigate how these factors influence audit delays in real estate and property firms listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023. The study employs purposive sampling in conjunction with multiple linear regression analysis, resulting in 200 samples. The results of this study indicate that audit delay tends to increase significantly when an extensive KAP audit is conducted on the company. Conversely, audit delay decreases considerably when the company obtains a particular audit opinion (such as an unqualified opinion), has a long-term relationship with the auditor (long audit tenure), shows a high level of profitability, and has a larger company size. This finding suggests that both auditor characteristics and company characteristics play a significant role in determining the timeliness of financial reporting simultaneously. In the meantime, audit delay is unaffected by solvency. In conclusion, the primary factors influencing the time it takes to complete an audit are internal company factors and the length of time spent working with auditors.